2009
DOI: 10.1021/la903564d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photocatalytic Properties of Mixed Polyoxometalate−Porphyrin Copolymers Obtained from Anderson-Type Polyoxomolybdates

Abstract: Hybrid polyoxometalate-porphyrin copolymeric films are obtained by the electro-oxidation of zinc octaethylporphyrin (ZnOEP) and zinc 5,15-dipyridinium octaethylporphyrin (5,15-ZnOEP(py)(2)(2+)) in the presence of the polyoxometalate [MnMo(6)O(18){(OCH(2))(3)CNHCO(4-C(5)H(4)N)}(2)](3-) (Py-POM-Py). These films allow the photocatalytic reduction of Ag(I)(2)SO(4) under visible irradiation in air in the presence of propan-2-ol at the 2D interface between water and the copolymeric films. The formation of metallic A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 118 publications
3
62
0
Order By: Relevance
“…This setup proved to be useful in the metal recovery of silver (Ag) where a complete reduction of the Ag + occurred and AFM studies on the film after the reaction showed no changes on the morphology. TEM studies revealed formation of silver particles that were inhomogeneous in size and shape [278]. However, when Zn II TPP is used instead of Zn II OEP no electron transfer could be observed onto the Anderson-Evans Mn III Mo 6 POM.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This setup proved to be useful in the metal recovery of silver (Ag) where a complete reduction of the Ag + occurred and AFM studies on the film after the reaction showed no changes on the morphology. TEM studies revealed formation of silver particles that were inhomogeneous in size and shape [278]. However, when Zn II TPP is used instead of Zn II OEP no electron transfer could be observed onto the Anderson-Evans Mn III Mo 6 POM.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…The modified properties of the inorganic diamine may be useful in both medical and nano-science research, in specific as recognition motifs and catalytically active sites where key amino acids may be replaced by POM amino acids. Schamming et al [278] has reported the synthesis of a hybrid POM-porphyrin copolymeric film with zinc octaethylporphyrin (Figure 12) Figure 13A consists of two types of POMs, Anderson-Evans and Lindqvist. Two monosubstituted hexamolybdates are covalently bound to one imido ligand on each side of the organically modified Anderson-Evans POM.…”
Section: An Overview Of Tris-functionalized Hybrid Structuresmentioning
confidence: 99%
“…For instance, Ruhlmann and coworkers used a polyoxometalate substituted by two pendant pyridyl groups to perform electropolymerization in presence of (OEP)-Zn (see Figure 23). 136 The copolymer obtained exhibited good properties in photocatalysis, where porphyrins played the role of photosensitizers in the visible domain for polyoxometalates known to be good photocatalysts usually only in the UV domain. While applications of this kind in the field of photocatalysis of hybrid porphyrin-polyoxometalate systems are now well established, 137,138 these hybrid copolymers could also have applications in photovoltaics, for instance.…”
Section: Use Of the Unsubstituted (Oep)zn Macrocycle As A Monomermentioning
confidence: 95%
“…In order to permit better control of the geometry of the polymers, (OEP)Zn macrocycles substituted by two protecting groups such as chlorides (see Figure 27B) 130,142 or pyridiniums 136 were used. In these cases, linear wires of polymers were obtained.…”
Section: Formation Of Linear Polymeric Chainsmentioning
confidence: 99%
“…Hybrid polyoxometalate-porphyrin copolymeric films were obtained by the electro-oxidation of zinc octaethylporphyrins in the presence of the Anderson hexamolybdate [MnMo 6 O 18 {(OCH 2 ) 3 CNHCO(4-C 5 H 4 N)} 2 ] 3− . These films were applied for the photocatalytic reduction of Ag I 2 SO 4 in the presence of propan-2-ol [273]. …”
Section: Polyoxometalate-based Hybrid Materialsmentioning
confidence: 99%